A simplified 2-D evaluation method of the arching effect for geosynthetic-reinforced and pile-supported embankments. (April 2015) - Lu, Weihua; Miao, Linchang
Abstract: The mechanical behavior of geosynthetic-reinforced and pile-supported (GRPS) embankments is under the influence of the soil arching effect. Several design methods have been proposed for estimating the magnitude of arching for GRPS embankments, but they are usually faced with two limitations: a pre-set constant critical arch height is assumed for the load calculation, and influences of the membrane effect of deflected geosynthetic and the resistance of compressible subsoil are poorly considered in supporting the embankment fill. To improve on these limitations, a new simplified method is presented for quantitatively evaluating the arching action, as well as the geosynthetic tension. During the derivation, the stress state and deformation condition within the arch rib can be coupled by mobilized shearing stress, which is correlated to the differential displacement between the pile (cap) and subsoil. Through comparative studies, it is found that the present method is validated as reasonable by field measurements and is in good agreement with several current design methods.